Condom use and HIV testing behaviours of men working in the construction industry in Western Cape, South Africa - Kweku Yakubu, Kamaluddin (Graduate School of Development Policy and Practice, 2025)
In 2017, UNAIDS published a report titled “Blind Spot: Reaching Out to Men and Boys”, which highlighted a global pattern where men experience worse outcomes than women in the HIV prevention and treatment cascade. This issue is particularly evident in South Africa, where men have been found to be less engaged in HIV prevention and treatment services compared to women. To address this disparity, targeted interventions are urgently needed to improve HIV- related health outcomes for men. However, many such interventions lack a clear theoretical foundation, making it difficult to replicate or assess their effectiveness. This study addresses this gap by empirically testing the Health Belief Model (HBM) and the Theory of Planned Behaviour (TPB) within a purposive sample of men who are at high risk for HIV/AIDS and hard-to-reach through traditional health facility-based interventions, male construction workers. The study found that an integrated model combining HBM and TPB constructs provided a statistically significant explanation of HIV testing and condom use. Key findings include the direct influence of perceived threat of HIV/AIDS, attitudes and subjective norms on HIV testing, and the significant role of self-efficacy and attitudes towards condom use on condom use intention. In addition to socio-demographic factors such as age and education, experiential factors associated with the impact of someday antiretroviral (ARV) therapy initiation under Universal Test and Treatment (UTT), such as knowledge of where to obtain ARVs, were also found to directly influence the HBM and the TPB, underscoring the importance of the evolving social context of HIV prevention and treatment in understanding HIV-related health outcomes. Finally, the study offers a structured approach for assessing and documenting theory-based interventions, facilitating systematic investigation and replication across different settings.